Estimasi Biaya Konstruksi Berdasarkan Eskalasi Biaya pada Pembangunan Bendungan Tipe Urugan dengan Regresi Linier Berganda - Alfriady Zuliansyah; Denik Sri Krisnayanti; Wati Asriningsih Pranoto (Journal of Creative Student Research, 2026)
Construction cost is one of the most important aspects determining the success of dam construction projects because it is directly related to project planning, budgeting, and cost control during implementation. Inaccurate cost estimation may lead to budget overruns, project delays, and reduced construction quality. This study aims to analyze the influence of reservoir storage capacity and diversion channel length on the construction cost of embankment dam projects using the multiple linear regression method. The research data were obtained from several embankment dam projects and analyzed using IBM SPSS Statistics software. The analytical procedures included classical assumption tests consisting of normality, multicollinearity, heteroscedasticity, and autocorrelation tests, followed by multiple linear regression analysis, partial significance tests, simultaneous significance tests, and coefficient of determination analysis. The results indicate that reservoir storage capacity and diversion channel length have a positive and significant effect on construction costs. The resulting regression equation is Y = 636.397 + 6.471X₁ + 0.960X₂, indicating that increases in reservoir storage capacity and diversion channel length will increase the construction cost of embankment dam projects. Both independent variables have significance values below 0.05, indicating that the proposed hypotheses are accepted. The developed regression model can be used as a reference for preliminary cost estimation of embankment dam projects, thereby supporting more effective, efficient, and accurate budgeting during the planning stage.